A review of recruitment and retention strategies in U.S. local health departments: insights and practical solutions - Houck, Olivia; Martin, Skky; Karnik, Harshada; Leider, Jonathon P.; Massuda Barnett, Gina; Hasbrouck, LaMar (Frontiers in Public Health, 2025)
IntroductionStaffing shortages in US local health departments (LHDs) have been well documented. While the increasing number of public health graduates offers an abundant talent pool, LHDs are facing increasing competition from other employers.MethodsWe conducted a comprehensive review to identify factors impeding recruitment and retention at LHDs and strategies that could be used to address them.ResultsOur findings highlight various barriers and opportunities. The main barriers were non-competitive salaries, perceived lack of employee autonomy, cumbersome HR protocols, and an environment that is not satisfying to a diverse workforce. Strategies to enhance recruitment include marketing the rewarding aspects of public health employment, establishing partnerships with academic institutions, and developing internship programs. Strategies to improve retention include improving the organizational work environment, supporting professional growth, mentoring programs, and succession planning.DiscussionOur study highlights the staffing barriers facing LHDs and offers practical solutions they can implement to support successful recruitment and retention. More work is needed to identify specific ways to improve workplace culture, quantify the disparity between pay offered by health departments and their competitors, and better understand barriers and opportunities related to supporting a diverse workforce.